Butanol recovery from synthetic fermentation broth via gas stripping - Nur Adrina, Ibrahim (2017)
ABE fermentation produces dilute acetone, butanol and ethanol products and required high energy consumption to separate the products during downstream process. In this study, gas stripping methods was used for butanol recovery process. Therefore, the objective of this experiment was to recover butanol from the synthetic fermentation broth via gas stripping based on the selected parameters. Two factorial design in Design-Expert® software was used to decide the range for each parameters selected. This research continued with the gas stripping experiment which was the main part for butanol recovery. Gas Chromatography (GC) with a flame ionization detector (FID) was used to analyze the samples. From the Design-Expert® software, the most contributing factor and interaction between the factors was analysed via two level factorial analysis. The ranking contribution factor of butanol recovery were butanol titre in feed > cooling temperature > stripping gas flow rate > feed temperature > gas stripping duration. Only butanol titre in feed (C) has negative effect meanwhile condenser cooling temperature (B) and interaction BC have positive effect on the butanol recovery. It is suggested to obtain the best condition for butanol recovery using Design-Expert® software testing on five factors related to gas stripping procedure which are: butanol titre in feed (20 g/L), feed temperature (60 ⁰C), stripping gas flow rate (1 L/min), cooling temperature (-10 ⁰C) and gas stripping duration (60 min). The results show that fractional factorial design is suitable in investigating the effect of large number of factors with a minimum number of experiments. Based on the experiment, the butanol recovery can be obtained until 88.18%. Thus, this project successfully achieved to recover butanol from the synthetic fermentation broth via gas stripping based on the predicted values of selected parameters.